Greywater Management in Educational Facilities: A Case of Bishop Senior Secondary School, Mukono - Desire Kobuzare (Uganda Christian University, 2025)
Greywater management in educational institutions presents a viable solution to water scarcity and sustainability challenges. This research focuses on design and implementation of a greywater management for Bishop Secondary School, Mukono. The research assessed the sources, volumes and characteristics of grey water generated within the school identifying key physical chemical and biological parameters. Preliminary tests indicated high BOD, COD, TSS, E. coli and TP values in comparison to the national standards. The main objective of this research and the design were achieved. The design consists of a batch treatment system using Kaolin clay as an adsorbent followed by filtration through a sand and gravel column. This will ensure that the grey water is treated to the required standards before reuse supplementing non drinking water needs such as toilet flushing and cleaning. The use of natural Kaolin clay enhanced the treatment process with high percentage reduction in all quality i.e. BOD, COD, TSS and TP with percentage reductions between 10% and 55%.
Undergraduate